If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2 + -3y) = -4y + -6 (2 * 2 + -3y * 2) = -4y + -6 (4 + -6y) = -4y + -6 Reorder the terms: 4 + -6y = -6 + -4y Solving 4 + -6y = -6 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 4 + -6y + 4y = -6 + -4y + 4y Combine like terms: -6y + 4y = -2y 4 + -2y = -6 + -4y + 4y Combine like terms: -4y + 4y = 0 4 + -2y = -6 + 0 4 + -2y = -6 Add '-4' to each side of the equation. 4 + -4 + -2y = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -2y = -6 + -4 -2y = -6 + -4 Combine like terms: -6 + -4 = -10 -2y = -10 Divide each side by '-2'. y = 5 Simplifying y = 5
| 14/tan40 | | 1-3n-3=-11 | | 2(m-20)=190 | | h(x)=1/2(x-2) | | 42-3x=14+11x | | 3/2x-(x-6)x | | 1+4=2 | | a/-12=25 | | 90=64.5+2y | | 7(-1+1x)=21 | | 16+r=25 | | -3(-1+3x)=111 | | 180=70+20+7x | | 7(5+2x)=-21 | | 4-(7*n)=12-(3n) | | y=x^2(-1) | | 120/2x | | 50+25x=10+30x | | x+1.5x=14200 | | 70c=49 | | -2x-6=4x | | 14=x+1.5x | | 9x-43x=76 | | 3y+9+10+6y+48y+120+30-6y= | | 5/3x-1/3=3 | | 11x+6(8x+3)=1670 | | 2a+3v=6.64 | | 8=3x+2x+8 | | 9/7=n/21 | | 1/9=a/18 | | 3v+2a=6.64 | | 2/4=a/12 |